2019
DOI: 10.1101/gad.324715.119
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome queuing enables non-AUG translation to be resistant to multiple protein synthesis inhibitors

Abstract: Aberrant translation initiation at non-AUG start codons is associated with multiple cancers and neurodegenerative diseases. Nevertheless, how non-AUG translation may be regulated differently from canonical translation is poorly understood. Here, we used start codon-specific reporters and ribosome profiling to characterize how translation from non-AUG start codons responds to protein synthesis inhibitors in human cells. These analyses surprisingly revealed that translation of multiple non-AUG-encoded reporters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 68 publications
7
58
1
Order By: Relevance
“…However, the short footprints persisted regardless of the duration and strength of CHX treatment (Supplementary Figure 1E), suggesting that CHX affects human and yeast ribosome profiling experiments differently. In agreement with our observation, short footprints in human cells can also be observed in a recently published dataset that uses CHX treatment for up to 24 hours (Supplementary Figure 1F) (37). This shows that the use of CHX in ribosome profiling has to be assessed for each organism and prompted us to analyze different parameters of translation, focusing on larger footprints for better comparability with previous publications.…”
Section: Cycloheximide Differentially Affects Human and Yeast Ribosomessupporting
confidence: 91%
“…However, the short footprints persisted regardless of the duration and strength of CHX treatment (Supplementary Figure 1E), suggesting that CHX affects human and yeast ribosome profiling experiments differently. In agreement with our observation, short footprints in human cells can also be observed in a recently published dataset that uses CHX treatment for up to 24 hours (Supplementary Figure 1F) (37). This shows that the use of CHX in ribosome profiling has to be assessed for each organism and prompted us to analyze different parameters of translation, focusing on larger footprints for better comparability with previous publications.…”
Section: Cycloheximide Differentially Affects Human and Yeast Ribosomessupporting
confidence: 91%
“…The crests of the waves are spaced by ~27 nts, a distance corresponding to the peak of the footprint length distribution (Figure 2-figure supplement 1), suggesting that this upstream density likely represents elongating ribosomes queued behind those arrested at stop codons. Even though ribosome collisions have been observed in bacteria and eukaryotes exposed to translation elongation inhibitors (Kearse et al, 2019;Mohammad et al, 2019), the extent of ribosome queuing in the Api-treated cells is especially pronounced. Because the queued ribosomes occupying inner codons of the ORFs carry nascent polypeptides they should be refractory to Api binding (Florin et al, 2017).…”
Section: Api-induced Translation Arrest At Stop Codons Results In Quementioning
confidence: 98%
“…A major goal of our laboratory has thus been to understand how the fates of noncanonical RNAs are controlled. This has led us in a variety of scientific directions and led to a number of unexpected findings, including mechanisms that control (i) circular RNA levels and localization (Liang and Wilusz 2014;Kramer et al 2015;Liang et al 2017;Huang et al 2018), (ii) non-AUG translation (Kearse et al 2019), and (iii) transcription elongation ), which will be the focus of this manuscript. We will summarize how a high-throughput RNAi screening effort revealed that the Integrator (Int) complex is a potent inhibitor of the transcription of many protein-coding genes.…”
mentioning
confidence: 96%